Central nervous system tumors in patients coming from areas of conflict in the Middle East/North Africa region: an experience from King Hussein Cancer Center - Obeidat, Mouness; Nazzal, Jamil; Al Sharie, Sarah; Al-Azzam, Ahmed Mahmoud; Maswadeh, Ahmad; Al-Abdallat, Haneen; Ismail, Layan; Alkderat, Marah; Hzayen, Ro’ya; Al-Sheble, Yasmeen; Mansour, Asem; Al-Hussaini, Maysa (Frontiers in Oncology, 2023)
Introduction: The global cancer burden has been disproportionately shifting towards low- and middle-income countries (LMICs). Limited availability and accessibility to screening, treatment and surveillance, increase in the prevalence and lack of control of risk factors, and underdeveloped healthcare infrastructures have greatly contributed to the disparity in the global cancer burden. Methods: A retrospective cohort study was conducted that included adult and pediatric patients with an established diagnosis of Central Nervous System (CNS) tumors including brain or spinal tumors of which different demographic, clinical characteristics, and financial burden were presented. Results: 749 patients were included stemming from various countries in the Middle East/ North Africa (MENA) region including Libya (34.2%), Palestine (19.8%), Iraq (15.4%), Syria (14.6%) Yemen (14.5%), and Sudan (1.5%). Most patients were adults (66%) with a median age of 34-year-old. 104 patients had died (13.9%), 80 patients were still alive (10.7%) and most of the patients (n= 565, 75.5%) were lost to follow-up. The added cost of managing these patients is 10,172,935 Jordanian Dinars (JOD), with King Hussein Cancer Foundation (KHCF) covering around 34.3% of the total cost. Conclusion: our study aimed at taking a closer look at patients coming from areas of conflict in the MENA region diagnosed and treated for CNS tumors at King Hussein Cancer Center over a 12-year period. It was found that even with the contributions of the Jordanian sources almost half of the patients were faced with the entire financial burden of treatment alone.